Transpedicular Screw Fixation of the Lumbar Spine: an anatomical perspective - Cheema, Omer Iqbal; Butt, Muhammad Tajammal; Shoaib, Tayyab; Irshad, Faiza; Nishat, Mufassar; Khan, Muhammad Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Background Transpedicular screw fixation of the lumbar spine is a popular procedure to attain stability in degenerative conditions, deformity and fracture. An inappropriate size and positioning of the screw however may result in postoperative neurological and vascular complications in up to 42% of cases emphasizing need for precise morphometric data. Aim: This study aimed at providing morphometric features of lumbar vertebral pedicles germane to transpedicular screw fixation in Punjab. Study design: Cross-sectional population study Methods: Lumbar spine measurements of height and transverse diameter of pedicles along with sagittal and transverse angles were recorded from CT scans of 33 adult males and 28 females using ImageJ1.47v radiological image processor. Distance along pedicular and sagittal axes reaching anterior cortex of vertebra (screw length) was also measured. Results: Vertical and transverse diameters of the pedicle were significantly larger in the male. Gradual increase from L1 to L5 in the sagittal and transverse angles was observed in both sexes. Both angles were comparatively larger in the females; transvers angle being much wider than the males. Depth (screw length) of anterior cortex along pediclular axis except at level L3 and parallel to sagittal axis was not significantly different in the two groups. Conclusion: The study has provided useful gender specific data which will be of interest to the researcher and may be useful for the operating surgeon in his preoperative assessment and deliberations of lumbar transpedicular screw fixation.